SHIPS WITH SMALL WATER-PLANE AREA: THE MAIN INFORMATION - Dubrovsky, Victor A. (International Journal of Research -GRANTHAALAYAH, 2021)
Ships with small water-plane area (below “SWA ships”) have very special shape of hulls. It is the reason of characteristic specificity of such ships. SWA ships usually are multi-hull ones. And as all multi-hulls, SWA ships differ from the comparable mono-hulls by bigger deck area relative the displacement and by simple ensuring of stability. There are some architectural types of SWA ships. Their differences are shown by the article. Relative area of deck and initial transverse stability of SWA ships are compared. Statistical data on performance: twin-hull SWA versus catamarans. Common specificity of and . The main external loads. Special method of designing. Main disadvantages. Conclusions, recommendation.